2011
DOI: 10.1007/s00464-011-2056-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the front abdominal wall as a potential factor leading to recurrence with laparoscopic ventral hernia repair

Abstract: The presented experiment adds new parameters to the understanding of in vivo mesh behavior. Elongation of the front abdominal wall may stretch implanted mesh and could be a cause of recurrence in cases of insufficient fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Experimental studies revealed that abdominal wall elongates approximately 11-32% under physiologic tension (approximately 16 N/cm). If high pressure is applied, the difference in dimensions may reach even 100% [38]. In such circumstances, implantation of standard, rigid prosthesis induces significant tension at the fixation points.…”
Section: Partially Absorbable Composite Implantsmentioning
confidence: 99%
“…Experimental studies revealed that abdominal wall elongates approximately 11-32% under physiologic tension (approximately 16 N/cm). If high pressure is applied, the difference in dimensions may reach even 100% [38]. In such circumstances, implantation of standard, rigid prosthesis induces significant tension at the fixation points.…”
Section: Partially Absorbable Composite Implantsmentioning
confidence: 99%
“…The aim of this study was to show the superiority of an elastic mesh concept (VS) versus a control, rigid mesh concept (PH) to confirm theoretical findings from the biomathematical model [14,16,19,20].…”
Section: Objectivementioning
confidence: 90%
“…In previous publications [14][15][16][17][18], the physiomechanical properties of available meshes and the tissue-implant link along with the junction forces were examined. To achieve that goal, we investigated the in vivo elasticity of the front abdominal wall and distinguished the strain zones [18].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations